A Fibrin Specific Monoclonal Antibody which Interferes with the Fibrinolytic Effect of Tissue Plasminogen Activator - Gargan, P E; Ploplis, V A; Scheu, J D (Thrombosis and Haemostasis, 1988)
Monoclonal antibodies to human fibrin have been prepared from stable hybridomas, obtained by fusion of a mouse myeloma cell line (NS-1) and spleen cells of Balb/c mice immunized with a suspension of human fibrin. One cell line, DG1, producing a monoclonal antibody of the IgG1 κ subclass, reacted specifically with human fibrin (KD = 1.2 nM). Western blotting analysis indicates that DG1 crossreacts with the fibrin fragment D-dimer. Using both a chromogenic and an 125I-fibrin release assay it was illustrated that in the presence of the fibrin specific antibody the t-PA mediated generation of plasmin was significantly inhibited.An animal model system, developed to monitor thrombosis and induced reactive fibrinolysis, was used to investigate the interference of plasminogen activation, by the antibody, in vivo.This fibrin specific antibody prolonged the onset of reactive fibrinolysis in a dose dependent manner.
Keywords: Fibrin specific antibody; Tissue plasminogen activator